2012
DOI: 10.1167/iovs.12-10388
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Unilateral Advanced Glaucoma

Abstract: There was no significant change in choroidal thickness of eyes with advanced open-angle glaucoma compared to that of fellow eyes with no glaucoma or with mild glaucoma. A thinner choroid does not necessarily indicate the presence of glaucoma, nor is a thicker choroid necessarily a surrogate for the absence of glaucoma. These observations further suggest a lack of relationship between open-angle glaucoma and choroidal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 40 publications
(53 reference statements)
4
41
0
Order By: Relevance
“…Therefore, clinical studies focused on choroidal (as a highly vascularized tissue) thickness in patients with NTG, and peripapillary choroidal thickness was found significantly thinner in these patients [13][14][15][16]. However, in terms of macular choroidal thickness, [13,17,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, clinical studies focused on choroidal (as a highly vascularized tissue) thickness in patients with NTG, and peripapillary choroidal thickness was found significantly thinner in these patients [13][14][15][16]. However, in terms of macular choroidal thickness, [13,17,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with glaucoma, decreased choroidal blood flow was clinically demonstrated, and it was associated with diminished central retinal function based on automated perimetry and pattern electroretinographic measurements [26]. However, most of the EDI-OCT studies did not provide convincing evidence to support the theory suggested by histopathological investigations [21][22][23]. On the other hand, choroid has a very dynamic nature, and choroidal circulation (and thickness) is significantly associated with ocular blood flow and cardiovascular status of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the included studies used Heidelberg Spectralis EDI-OCT (Heidelberg Engineering, Heidelberg, Germany) to obtain choroidal thickness data. In addition, there were 2 studies using Cirrus HD-OCT (Carl Zeiss Meditec, Dublin, CA), 42,46 1 study using RTVue-100 SD-OCT (Optovue Inc., Fremont, CA), 43 and 1 study using swept-source high-penetration OCT (SS-OCT) 30 which is a prototype introduced by Yasuno et al 47 There were 15 studies containing choroidal thickness data under the fovea 25,26,[28][29][30][31]35,[38][39][40][41][42][43]45,46 and 10 articles reporting choroidal thickness data surrounding the ONH. 25,27,[32][33][34][36][37][38]42,44 One of the 15 studies on subfoveal choroidal thickness (SFCT) included 3 study groups, so we separately compared the normal control group with the other 2 OAG patient groups (POAG group and NTG group).…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…For these reasons, we chose the SFCT data and the average PCT to be pooled. 25,26,[28][29][30][31]35,[38][39][40][41][42][43]45,46 between OAG patients and controls found significant heterogeneity (I 2 = 85.1%) across the articles, so the data were pooled through the random-effects model. The meta-analysis of these data showed that the SFCT in OAG patients was not significantly thinner compared with that in controls (WMD = À7.94; 95% confidence interval, À 26.01 to 10.13; P = 0.389, Fig.…”
Section: Meta-analysis Of Choroidal Thicknessmentioning
confidence: 99%
“…Other investigations demonstrated that the choroid is abnormally thick in eyes with central serous choroidoretinopathy and in those with polypoidal choroidal vasculopathy, while it is abnormally thin in eyes with myopic retinopathy [7,8,9,10,13,14]. The results of various studies have remained inconclusive on whether eyes with open-angle glaucoma, angle-closure glaucoma, diabetic retinopathy and retinal vein occlusion have an abnormally thick choroid [7,18,19,20,21,22,23,24]. The findings of our study add ISCNV to the list of diseases associated with a thickened choroid.…”
Section: Discussionmentioning
confidence: 99%